Efektifitas Penggunaan Macromedia Flash 8 Terhadap Penguasaan Kosakata Bahasa Arab Santriwati Shof I Reguler - Muhammad Munir; Fathinatul Baqiyah; Aida Kumala Sari (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
TMI Al-Amien Prenduan Islamic boarding school is one of the Islamic boarding schools in Madura that requires students and students to speak Arabic and English in their daily lives. However, researchers found that many regular class I students still did not master basic and easy Arabic vocabulary so researchers wanted to experiment with one of the learning media, Macromedia Flash 8, which might make it easy for them to master Arabic vocabulary. Indeed, the purpose of this study is to determine the effectiveness or use of macromedia flash 8 on mastery of Arabic vocabulary of students of the first year TMI Pi Al-Amien Prenduan Sumenep Madura and to find out how effective the use of the media is. This research is an experimental quantitative study, by taking data from students of the first year of TMI Pi Al-Amien Prenduan Sumenep Madura with a total sample of 65 from a population of 219 students. The collection of data using tests, namely pre-test and post-test and use documentation. Data analysis techniques in this study used the manual T test. From the results of the data analysis, it was concluded that the use of Macromedia Flash 8 was effective against the mastery of Arabic vocabulary of students of the first TMI Regular Pi Al-Amien Prenduan Sumenep Madura with a final value of 0.207> 0.126 with a significance value of 0.55.